Hadith #2615 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Salah bin Abi al-Akhdr صالح بن أبي الأخضر اليمامي مولى هشام (Sunan Abi Dawud)
Ibn “umar said “The Apostle of Allaah(ﷺ) burned the palm tree of Banu Al Nadr and cut (them) down at Al Buwairah. So, Allaah the exalted sent down “the palm trees you cut down or left.”
Grade: Sahih